Efektifitas penggunaan alat I-Perisalah dalam kegiatan konvensi Studi Kasus: Sidang Tahunan MPR RI Tahun 2018 - Velerie Samallo (Bisnis Event, 2023)
This study intends to determine an Indonesian speech recognition system that is used to transcribe speeches/meetings automatically. This I-perisalah application has the feature of converting someone's speech into writing so it is easy to know when, and what to talk online. At the time of Sidang Tahunan MPR RI, the minutes must be made after each session or meeting and then the results of the minutes will be given to each bureau. This tool can facilitate the reporter when making minutes of a meeting or conference. In this study the method used is a qualitative research method. While the type of research is descriptive, which means that research is conducted to find out and be able to explain the characteristics of the variables under study in a situation. Data collection techniques carried out with primary data and secondary data, where data is obtained directly from the object of research through interviews. While secondary data is obtained from library studies and online searches through the world wide web. The results of this study indicate that the process of making the minutes will be effective and efficient by using the i-perisalah application during the Sidang Tahunan MPR RI in 2018.